PERANAN BADAN KOORDINASI BANTUAN PEMANTAPAN STABILITAS NASIONAL (BAKORSTANAS) DAERAH JAWA TIMUR TAHUN 1988-2000 - Wulandari, Dela; Sasmita, Nurhadi; Widuatie, Ratna Endang (Historia, 2021)
This paper discusses the role of the National Stability Assistance Coordination Agency (Bakorstanas) of East Java in 1988-2000. The purposes of this study are to provide an overview of the background of the establishment of East Java Bakorstanasda, to examine the role of East Java Bakorstanasda, and to investigate the impact of the existence of East Java Bakorstanasda. The method used in this study was a historical method consisting of four stages, namely: heuristics, source criticisms, interpretation, and historiography. The approach used is political sociology with hegemony theory and democracy theory. The results of this study indicate that East Java's Bakorstanasda was an institution formed by Suharto as the controller of the New Order's authority in its social and political authoritarianism. Bakorstanada East Java had an important role in the Suharto government. During the Soeharto government, East Java's Bakorstanasda was used as a means of controlling Suharto's power at the regional level especially East Java. The existence of East Java Bakorstanasda also had a negative impact. The negative impact caused by the duty and authority of the police was limited, the East Java Bakorstanasda also obscured the negative sides of its members because it was reluctant to accept criticism from the public accompanied by acts of deprivation, interrogation, kidnapping, and repressive actions to civilians. Keywords: Bakorstanasda; East Java; social politics.